Rural-urban variation in hypertension among women in Ghana: insights from a national survey - Francis Appiah; Edward Kwabena Ameyaw; Joseph Kojo Oduro; Linus Baatiema; Francis Sambah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Eugene Budu (BMC, 2021)
Abstract Background Hypertension is one of the leading causes of cardiovascular morbidities in Ghana and represents a major public health concern. There is dearth of information on the rural-urban disparity in hypertension among women in Ghana. Therefore, this study aimed at examining the rural-urban variation in hypertension among women in Ghana. Methods We extracted data from the women's file of the 2014 Ghana Demographic and Health Survey. The sample included 9333 women aged 15-49 with complete data on hypertension. The analysis was done using Pearson Chi-square and binary logistic regression at 95% confidence interval. The results of the binary logistic regression were presented as Odds Ratios (ORs) and Adjusted Odds Ratios (AORs). Statistical significance was set at p < 0.05. Results Hypertension prevalence among urban and rural residents were 9.5% and 5.1% respectively. Rural women had lower odds of hypertension [OR = 0.59; 95% CI = 0.52, 0.67] compared to urban women, however, this was insignificant in the adjusted model [aOR = 0.84; 95% CI = 0.70, 1.00]. The propensity to be hypertensive was lower for women aged 15-19 [aOR = 0.07; 95% CI = 0.05, 0.11]. The poorest were less likely to be hypertensive [aOR = 0.63; 95% CI = 0.45, 0.89]. Single women were also less probable to have hypertension [aOR = 0.66; 95% CI = 0.46, 0.97]. Conclusions Women from urban and rural areas shed similar chance to be hypertensive in Ghana. Therefore, the health sector needs to target women from both areas of residence (rural/urban) when designing their programmes that are intended to modify women's lifestyle in order to reduce their risks of hypertension. Other categories of women that need to be prioritised to avert hypertension are those who are heading towards the end of their reproductive age, richest women and the divorced.